PENGARUH FASILITAS BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA SMP - sawaluddin, sawaluddin; Suarman, Suarman; Trisnawati, Fenny (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
This study was motivated by the number of students who obtained low learning outcomes. This study aims to analyze the effect of learning facilities and learning motivation on student learning outcomes. The research was conducted at SMP Negeri 32 Pekanbaru Class VII Social Studies Subject. The sample in this research was 67 students who used proportional random sampling technique. Data obtained through documentation and questionnaires, then analyzed using descriptive analysis and multiple linear regression. The results showed that learning facilities and learning motivation both partially and simultaneously had a positive and significant effect on learning outcomes. The results of the t test of the effect of learning facilities on learning outcomes with a value of Sig. 0.012 < 0.05 the value of t count 3.091> t table 1.997, the effect of learning motivation on learning outcomes with a value of Sig. 0.003 <0.05 the value of t count 2.597> t table 1.997 then the effect of learning facilities and learning motivation on learning outcomes with a Sig value. 0.000 <0.05 the value of f count of 15.673> f table 3.14. The coefficient of determination (R2) value is 32.9%. This shows that the more adequate the student learning facilities, the more student learning outcomes will increase and the higher the student learning motivation, the higher the student learning outcomes.